5-Amino-2-aryl-1, 2, 3-triazol-4-carboxylic acids: Synthesis, photophysical properties, and application prospects. (July 2020) - Safronov, Nikita E.; Fomin, Timur O.; Minin, Artem S.; Todorov, Lozan; Kostova, Irena; Benassi, Enrico; Belskaya, Nataliya P.
Abstract: To enlarge the highly active fluorophore family of small molecular heterocycles, we present an effective strategy for the synthesis of novel 2-aryl-1, 2, 3-triazol-4-carboxylic acids (ATAs). The behavior of ATAs in different solvents showed that these new 1, 2, 3-triazole derivatives had bright blue fluorescence with excellent quantum yields, large Stokes shifts, and prolonged fluorescence lifetimes. Their photophysical and physicochemical properties showed extra sensitivity to both structural changes and the microenvironment, usually accompanied by marked changes in quantum yield. The responses of the ATAs to varying pH were different depending on the structure of the amino group at the triazole ring C5 atom. pKa values of 7.65–8.08 were obtained for ATAs bearing a tert- amino group. In contrast, the pKa values of ATAs bearing secondary alkylamines were in the range of 3.20–3.52. Quantum mechanical methods were employed to understand the underlying transitions and explain the obtained experimental data. Among the synthesized compounds, aggregation-induced emission enhancement (AIEE) behavior was observed, with potential applications as sensors for monitoring and controlling pH. The reversibility of ATAs between acid and alkaline pH values, as well as their toxicity, supports their real-time use in biological research. Graphical abstract: Image 1 Highlights: New 2-aryl-1, 2, 3-triazol-4-carboxylic acids with bright blue fluorescent and prolonged fluorescence lifetimes were obtained. Among the synthesized compounds, aggregation-induced emission enhancement behavior were found. Fluorescence intensity was very sensitive to structural changes and the microenvironment. Triazole acids have displayed potential applications for monitoring pH in biological fluids in real-time.